Benefit of Flexible Working Hours on Employee Performance in Nepalese Commercial Banks - Pandey, Swopnil Raj (Nepalese Journal of Economics, 2025)
This study examines the benefits of flexible working hours on employee performance in Nepalese commercial banks. Employee performance is the dependent variable. The selected independent variables are work life balance, job satisfaction, job motivation, stress level, and work load management. The primary source of data is used to assess the opinions of respondents regarding work life balance, job satisfaction, job motivation, stress level, work load management, and employee performance. The study is based on primary data of 126 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of benefits of flexible working hours on employee performance in Nepalese commercial banks. The study showed a positive impact of job satisfaction on employee performance. It indicates that higher the job satisfaction, higher would be the employee performance. Similarly, the study showed a positive impact of work life balance on employee performance. It indicates that higher the work life balance, higher would be the employee performance. Likewise, the study also showed a positive impact of job motivation on employee performance. It indicates that higher the motivation from the job, higher would the employee performance. Further, the study showed a negative impact of stress level on employee performance. It indicates that higher the stress level, lower would be the employee performance. In addition, the study showed a positive impact of work load management on employee performance. It indicates that proper process of forecasting, planning, distributing, scheduling, and monitoring people’s workload on organizations lead to increase in employee performance.